Language development - Brooks, Patricia (Patricia J.); Kempe, Vera. (Chennai BPS blackwell, 2012)
"An accessible introduction to language development aimed at a wide audience of students from different disciplines such as psychology, behavioural science, linguistics, cognitive science, and speech pathology. It requires only minimal knowledge of psychology, and is intended for undergraduates from the second year of studies onwards. The wide accessibility to undergraduates is achieved by avoiding technical terminology when possible and explaining all crucial concepts in the text. From the first moment of life, language development occurs in the context of social activities. This book emphasises how language development interacts with social and cognitive development, and shows how these abilities work together to turn children into sophisticated language users--a process that continues well beyond the early years. Covering the breadth of contemporary research on language development, Brooks and Kempe illustrate the methodological variety and multi-disciplinary character of the field, presenting recent findings with reference to major theoretical discussions. Through their clear and accessible style, readers are given an authentic flavour of the complexities of language development research.With such research advancing at a rapid pace, Language Development uncovers new insights into a variety of areas such as the neurophysiological underpinnings of language, the language processing capabilities of newborns, and the role of genes in regulating this amazing human ability. "--
"In this book, we will try to understand what language development entails and what lies behind this extraordinary human achievement"--
1. What enables infants to acquire language? 2. What do infants learn before they speak their first word? 3. How does social change and cognitive development support language development? 4. How do children learn words? 5. How do children learn to combine and modify words? 6. What kind of language do children encounter? 7. How do children learn to use language? 8. How does language development affect cognition? 9. What is the role of literacy in language development? 10. What causes language impairments? 11. How do deaf children acquire language? 12. How does language development affect the brain?
Includes bibliographical references (pages 303-366) and index.
Keywords: Language acquisition; Psycholinguistics